Perempuan Usia Muda Penderita DM Tipe 2 dengan Multikomplikasi: Laporan Kasus - Adhalia, Lian; Mahmuda, Iin Novita Nurhidayati (PT Kalbe Farma Tbk., 2024)
Type 2 diabetes mellitus is a progressive chronic metabolic disease characterized by an increase in blood sugar due to insulin resistance. Uncontrolled diabetes will cause various acute and chronic complications. The case is a young DM patient with complications of hyperosmolar hyperglycemia status, cerebral ischemia, and pressure ulcers.